Studi Kualitas Air pada Pembesaran Ikan Mas Koki (Carassius auratus) di Sukabumi [Water Quality Study Of Goldfish (Carassius auratus) Enlargement In Sukabumi] - Abdul Manan; Bagus Rizki Novianto (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Water is a place for aquatic organisms and other organisms to live. Water must fulfill a number of factors that support the factor of chemistry, physics and biology. Most of the cultivation death caused by these factors. The conduct of this study is to know the water quality in the enlargement process in Central goldfish Freshwater Aquaculture Development (BBPBAT) Sukabumi. Study are carried out at the Hall for Development of Freshwater Aquaculture, Selabatu Village, Cikole District, Sukabumi Regency, West Java Province, on January, 16 - February 16, 2012. The methods that used is descriptive method.This type of goldfish cultivation is owned by the government. Sources of water used in rearing goldfish come from Cisarua river by using irrigation systems. The source of this water has a temperature between 23.5 – 24.3°C, pH 6.24 – 7.02, dissolved oxygen 4.73 – 4.61 mg/l, dissolved carbon dioxide 11,04 – 25,87 mg/l, ammonia 0.52 – 0.58 mg/l, and nitrite 0.046 – 0.059 mg/l. Monitoring water quality at the source of water every month, while the water quality monitoring in the goldfish pond enlargement is done every week to determine the feasibility of water used for aquaculture activities.